Interaction between feeding rate and area for periphyton in culture of Nile tilapia juveniles - doi: 10.4025/actascianimsci.v34i2.12469 - Rebouças, Vanessa Tomaz; Caldini, Nayara Nunes; Cavalcante, Davi de Holanda; Silva, Francisco Jackes Rodrigues da; Sá, Marcelo Vinícius do Carmo e (Acta Scientiarum. Animal Sciences, 2011)
The objective of the present work was to determine the effects of the interaction between feeding rate and area for periphyton in rearing aquaria for Nile tilapia. Twenty 25 L polyethylene outdoor aquaria were used to hold experimental fish. Three tilapia fingerlings (2.56 ± 0.14 g) were stocked in each aquarium for five weeks (12 fish m-2). There were two different feeding rates (full and full minus 30%) and two submerged areas for periphyton development (59.4% and 96.5% of the aquarium surface area; n = 5). Final body weight, specific growth rate and yield in the 96.5%-area aquaria of fish submitted to 30% less feed were significantly higher than in the 96.5%-area aquaria submitted to full feeding rates. Fish growth in the restricted-feed aquaria was favored by their better water quality (higher pH and lower total ammonia nitrogen). There were negative effects on final body weight, SGR, yield and feed conversion ratio of fish in full-feed aquaria when the area for periphyton increased from 59.4 to 96.5%. It was concluded that the combination of restricted feeding rates with large substrate areas for periphyton growth results in better water quality for fish culture than the adoption of each management alone.